Outsourcing of Information Technology and Business Processes in Poland: Motivations and Environmental Factors - Wojciech Piotrowicz; Damian Kedziora (Managing Global Transitions, 2018)
The aim of the paper is to summarise the literature focused on Information Technology and Business Process Outsourcing in Poland and to contribute to understanding of motivations and environmental factors driving service relocations to Central and Eastern Europe. This exploratory study is based on academic literature and two data sources: government and industry reports, as well as small-scale exploratory survey. The findings confirm the cost reduction to be the main driver, followed by the willingness to improve processes and business performance. The substantial advantage of Poland is human resources – the availability of highly skilled, well-educated workforce at relatively low cost. Even though the salaries are often higher than in Asia, it is compensated by the number of graduates and knowledge of foreign languages.Membership of the European Union and political stability also plays an important role. This exploratory study, aside of relocation trends overview, enabled the views among service providers to be captured and compared with the commercial and governmental reports.